2015
DOI: 10.1097/mpg.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Morphometry and Small Bowel Permeability in Children With Portal Hypertension

Abstract: PHT is often associated with duodenopathy. SIP does occur as a result of increased paracellular permeability. Factors of increased SIP, undernutrition, and PHTD do not have correlation in childhood PHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…66 A study in children with portal hypertension reported villous atrophy, capillary dilation, muscularis mucosae thickening, and increased intestinal permeability. 67 In a study in Austria, patients with severe portal hypertension had increased gastroduodenal and intestinal permeability, which was correlated with the degree of the hepatic venous pressure gradient. As markers of the enteric bacteria translocation, lipopolysaccharide (LPS)-binding proteins and interleukin-6 had increased serum levels in patients with portal hypertension patients compared with controls.…”
Section: Role Of the Intestinal Chemical Barrier In The Nafld Develop...mentioning
confidence: 99%
“…66 A study in children with portal hypertension reported villous atrophy, capillary dilation, muscularis mucosae thickening, and increased intestinal permeability. 67 In a study in Austria, patients with severe portal hypertension had increased gastroduodenal and intestinal permeability, which was correlated with the degree of the hepatic venous pressure gradient. As markers of the enteric bacteria translocation, lipopolysaccharide (LPS)-binding proteins and interleukin-6 had increased serum levels in patients with portal hypertension patients compared with controls.…”
Section: Role Of the Intestinal Chemical Barrier In The Nafld Develop...mentioning
confidence: 99%
“…Despite some progress in understanding bacterial translocation mechanisms in BA, there remain many unanswered questions, and in particular, data is limited in paediatrics. Urinary excretion of melibiose/rhamnose did suggest increased intestinal permeability in children with cirrhotic portal hypertension but details on disease aetiology were limited (66). One paediatric study revealed an increase in serum markers for intestinal wall integrity in cholestatic versus healthy infants, but could not differentiate BA versus non-BA cholestatic subgroups, suggesting infant cholestasis, indiscriminate of cause, may be associated with intestinal epithelial damage (67).…”
Section: Biliary Atresiamentioning
confidence: 99%
“…In the study from the authors’ center, children with EHPVO showed features of enteropathy as evident by duodenal morphometric features (60%). The features were lower villous to crypt ratio, dilated capillaries, increased thickness of muscularis mucosae) and increased small intestinal permeability (lactulose excretion test) as compared to healthy controls[ 61 ]. Portal hypertensive enteropathy is one of the most important causes of growth failure in children.…”
Section: Ehpvomentioning
confidence: 99%